Comparison of Ischemic Preconditioning and Systemic Piracetam for Prevention of Ischemia-Reperfusion Injury in Musculocutaneous Flaps - Demiröz, Anıl; Derebaşınlıoğlu, Handan; Ercan, Alp; Arslan, Hakan; Aydın, Övgü; Ekmekçi, Hakan; Balcı Ekmekçi, Özlem; Aydın, Yağmur (Journal of Reconstructive Microsurgery, 2020)
Background Ischemia-reperfusion injury plays an important role in flap failure. Ischemic preconditioning technique is the only proven method for preventing ischemia-reperfusion injury, but it is not used widely in daily practice because of difficulties such as prolonging the operation time, need for surgical experience, and increasing the risk of complications. This study has been performed with the assumption that piracetam may be a simple and inexpensive alternative to the preconditioning technique due to its antioxidant, antiaggregant, rheological, anti-inflammatory, antiapoptotic, cytoprotective, and immune modulating effects.Methods Thirty-two rats were divided into four groups and latissimus dorsi musculocutaneous flaps were raised. No extra procedure was applied, and no treatment was given to the control group. Four hours of ischemia was created by clamping the thoracodorsal pedicle in the second group. The animals in the third group were treated with 10 minutes of ischemia and reperfusion periods as a preconditioning procedure before the 4 hours of ischemia. Animals in the fourth group received systemic piracetam 30 minutes before and 6 days after reperfusion. Nitric oxide and myeloperoxidase levels in serum and tissue, acute inflammatory cell response, and vascular proliferation in tissue were examined at the postoperative 24th hour and 10th day.Results Myeloperoxidase activity in both preconditioning and piracetam groups, was significantly lower than the ischemia-reperfusion group. Acute inflammatory cell response was similarly decreased in both preconditioning and piracetam groups compared with ischemia-reperfusion group. Tissue measurements of nitric oxide were also significantly higher in both preconditioning and piracetam groups than in the ischemia-reperfusion group. However, vascular proliferation increased in the preconditioning group, while it did not show any significant change in the piracetam group.Conclusion This study shows that systemic piracetam treatment provides protection against ischemia-reperfusion injury in musculocutaneous flaps and can offer a simple and inexpensive alternative to the preconditioning technique.
Keywords: ischemia-reperfusion injury; latissimus dorsi; microvascular free flap operations; piracetam